Exercise tolerance and skeletal muscle structure and function in patients with severe chronic heart failure - Derman, Kirsten Louise (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Fatigue and exercise intolerance are common symptoms experienced by patients with chronic heart failure (CHF). Historically it has been argued that central cardiopulmonary factors including pulmonary congestion and reduced lung compliance cause dyspnoea that limits the exercise tolerance of such patients. But recent studies have indicated that exercise capacity in patients with CHF may not be limited solely by central cardiorespiratory factors. Rather the focus has shifted to aspects of the peripheral circulation and skeletal muscle function as possible factors limiting the exercise tolerance of patients with CHF. However there are few studies describing both the structural and functional abnormalities in the skeletal muscle of patients with CHF. In the first study of this dissertation, 11 patients with end-stage heart failure (NYHA class Ill-IV) and 10 healthy control subjects (C) underwent i) graded exercise to exhaustion for determination of peak oxygen consumption (VO₂ peak) and peak work load (Wlpeak); ii) isometric and isokinetic tests of skeletal muscle function and iii) radionuclide angiography for determination of ejection fraction (EF%). VO₂ peak (12.5 ± 1.0 vs 34.3 ± 3.5 mlO₂fkg/min; p<0.001), Wlpeak (73 ± 10 vs 224 ± 14 W; p<0.001), total work performed by the quadriceps muscles (TWQ) in a 30 sec isokinetic test (TWQ; 1565 ± 166 vs 2892 ± 345 J; p<0.05), and hamstring muscles (TWH) (TWH; 604 ± 163 vs 2003 ± 326 J; p<0.05), maximum voluntary isometric contraction (MVC) of the quadriceps muscles (MVC; 134 ± 12 vs 194 ± 11 Nm; p<0.001) and isokinetic peak torque of the ~uadriceps (PKTQ) (PKTQ; 133 ± 15 vs 203 ± 23 Nm; p<0.05) and hamstring muscles (PKTH) (PKTH; 60 ± 8 vs 108 ± 16 Nm; p<0.05) and time to fatigue during a test of isometric endurance (68 ± 12 vs 100 ± 10 sec; p<0.05) were all significantly lower in patients with CHF. However when corrected for the reduced lean thigh volume (muscle mass) in patients with CHF, PKTQ, PKTH and MVC were no longer different from control values. But the total work performed by the quadriceps and hamstring muscles in a 30 second isokinetic test was reduced even when corrected for the reduced lean thigh volume in patients with CHF. Furthermore, patients with CHF terminated progressive cycle exercise to exhaustion at heart rates, rates of ventilation, respiratory exchange ratios and blood lactate concentrations that were significantly lower than values achieved by control subjects during maximal dynamic exercise. These data suggest that skeletal muscle functional abnormalities including a decreased resistance to the development of fatigue exist in patients with severe CHF. In the second study of this dissertation, 10 patients with CHF who participated in the first study and eight control subjects underwent a skeletal muscle biopsy of the vastus lateralis muscle for light and electron microscopic analysis. Significant histological and ultrastructural changes were found in all SM biopsies from patients with CHF. These included atrophy and hypertrophy of fibres, fibre splitting, internalized nuclei, nuclear knots, moth-eaten fibres, increased lipid droplets. Electron microscopy showed a large variety of nonspecific abnormalities, including mitochondrial changes, Z-band degeneration and accumulation of intracellular glycogen. Ultrastructural morphometry revealed capillary basement membrane width significantly increased in the SM of patients with CHF, (409 ± 13 vs 121 ± 3 nm; p<0.01). A novel, blinded, impartially scored method for grading SM pathology showed that SM biopsies of patients with CHF had higher scores for myopathic changes compared to C (12.0 ± 1.5 vs 1.6 ± 1.0 arbitrary units; p<0.05). SM pathology score correlated significantly with VO₂ peak, Wlpeak, and TWQ (p<0.05 to p<0.02) but not with EF%. EF% did not correlate with either VO₂ peak, Wlpeak or TWQ. These data support the hypothesis that: i) severe SM structural and functional abnormalities may limit exercise capacity in patients with CHF; ii) the severity of SM pathology but not resting systolic cardiac function, predicts exercise performance in patients with CHF.